Review of the activities of the Moscow discussion club of the International Public Organization “Association of Researchers of the Golden Horde” - Belyakov A.V. (Золотоордынское обозрение)
This article is a brief overview of the activities of the Moscow discussion club of the International Public Organization “Association of Researchers of the Golden Horde”. The Moscow discussion club began its work only in the spring of 2021. Within its framework, more than a dozen different events were held in online and offline formats, from thematic reports to presentations of new publications on the theme of the Golden Horde. Within the framework of this article, we will not only provide a list of such scientific events over the entire existence of the Moscow discussion club of the International Public Organization “Association of Researchers of the Golden Horde”, but also offer a report about the content of certain reports, and identify the features of research that were represented during the activities of the department. We will also propose a work plan for the Moscow discussion club up to the end of 2022, accepting, of course, that there may be some changes. We hope with this article to attract the interest of a wide range of researchers of the history of the Golden Horde to, first of all, the very fact of the existence of the “Association of Researchers of the Golden Horde”. Secondly, we hope to intensify joint cooperation in popularizing the study of the history of the Golden Horde and its heritage, building contacts between researchers and holding various future scientific events, including within the framework of work by the Moscow discussion club of the “Association of Researchers of the Golden Horde”.